Occurrence of variants with temperature-dependent susceptibility (TDS) to antibiotics among Stenotrophomonas maltophilia clinical strains - Hejnar, P; Kolár, M; Hájek, V; Koukalová, D; Hamal, P (Folia microbiologica, 2001)
Susceptibility to 20 antibiotics was tested in 104 Stenotrophomonas maltophilia strains at 37 and 30 degrees C by means of a dilution micromethod to verify the phenomenon of temperature-dependent susceptibility (TDS). Trimethoprim-sulfamethoxazole, pefloxacin and ofloxacin were the most active preparations at 37 degrees C (93, 90, and 86% of susceptible strains, respectively), whilst trimethoprim-sulfamethoxazole, cefoperazone-sulbactam and pefloxacin performed best at 30 degrees C (94, 94, and 76% of susceptible strains, respectively). Variants 37TDS (minimum inhibitory concentration, MIC, of tested antibiotics at least 4-times lower at 37 than at 30 degrees C) occurred in 60%. Variants 30TDS (at least 4-times lower value of MIC at 30 than at 37 degrees C) were found in 7.7%. Both variants in susceptibility to tested antibiotics appeared in 23.1%, whilst neither of them was observed in 9.6%. The 37TDS phenomenon was recorded most of all with gentamicin (51% of strains), amikacin (47), colistin (44) and tetracycline (34). The 30TDS phenomenon was found particularly with cefoperazone-sulbactam (16.0% of strains) and colistin (10.0%). The above phenomena may be due to changes in membrane permeability, temperature-dependent ribosomal changes, and insufficient adaptation to higher temperatures of some strains of the originally environmental species S. maltophilia.
Keywords: Drug Resistance, Bacterial; antibakteriální látky; Temperature; Microbial Sensitivity Tests; teplota; Genetic Variation; mikrobiální testy citlivosti; Anti-Bacterial Agents; genetická variace; bakteriální léková rezistence; Stenotrophomonas maltophilia